(untitled) (Research, Society and Development, 2022)
The objective of the present work was to evaluate the application of the inoculant Bradyrhizobium Japonicum and its consequences on soybean nodulation, with the intention of showing in practice the efficiency that this method brings, proving positive results, provided that they are well managed. This work had the purpose of showing the viability of applying inoculants in soybean crops manually through a comparative experiment, in soils not cultivated with soybeans. Two different experiments were carried out in pots from March 2022 on an Oxisol, with the same methods and different treatments. Ten treatments were tested: (t1) inoculated and 10 treatments: (t2) control. Shoot length (CM), root length (CM), number of leaves (UN), plant weight (G), root weight (G) were evaluated. The best nodulations were obtained with inoculant application. Lower values ​​of results were obtained in the control treatments.